Improving Elementary Students' Science Literacy Through Game-Based Learning Supported By Baamboozle Media - Lathifah, Iva; Jupriyanto, Jupriyanto (Universitas Pakuan, 2025)
The aim of this research is to analyze the effectiveness of using Baamboozle media in increasing the scientific literacy of fifth grade students on the structure of the earth's layers. This research uses a one group pretest-posttest design in a quantitative approach. The research participants were 29 fifth grade students at an elementary school. Data was collected using essay-based instruments that have been validated and tested for reliability. The results of the analysis showed a significant increase in the average student score, from 48.65 on the pretest to 80.44 on the posttest. Paired samples t-test analysis indicated that the use of Baamboozle significantly increased students' understanding of scientific concepts. Apart from improving learning outcomes, this media has also been proven to make learning more interesting, encourage teamwork, and increase student motivation in participating in the learning process. This research provides a new perspective on the effectiveness of Baamboozle in science education, while strengthening previous findings about the benefits of game-based learning in the classroom.